AI-Driven Personalization: Revolutionizing E-commerce with Blockchain and IoT Collaboration - Celestin, Mbonigaba (RIRAI Publisher, 2025)
This study investigates the transformative potential of Artificial Intelligence (AI), Blockchain, and the Internet of Things (IoT) in revolutionizing e-commerce personalization. Utilizing a qualitative methodology, it incorporates systematic literature reviews, secondary data analysis, and expert interviews. Findings reveal an 87.5% increase in customer retention rates due to AI-driven personalization from 2020 to 2024, with blockchain adoption reducing fraud cases by 80% and boosting transaction volumes by 540% over the same period. IoT integration achieved a ninefold rise in device use, driving a 45% reduction in logistics costs. The synergy of these technologies has addressed personalization challenges while enhancing security and operational efficiency. The study concludes with a call for adopting integrated frameworks, prioritizing ethical AI models, and scaling IoT adoption to sustain innovation in e-commerce.